THE LEADERSHIP STYLE TOWARD STUDENT’S PERFORMANCE AS EVENT ORGANIZER OF ECONOMIC CARE DAY - Sarinah, Sarinah (Dinasti International Journal of Management Science, 2019)
The aims of the study was to see the leadership style toward students’ performance as event organizer of 'Economic Care Day' held by students. Quantitative becomes a method in this study. Meanwhile, data was analyzed with SPSS 19 tools using a simple linear regression test. Research Data was collected through observations, questionnaires and documentation. The research sample was students of Semester IV (four) class B in the economic education study program of STKIP YPM that contracted leadership courses. Based on data, it was known that the research results show that: there was a significant influence between the leadership style toward the student's performance in the events in the Economic’s Care Day. It can be seen from the ability of team leaders in establishing cooperation and coordination relationship with various parties, especially among the organizer team, in this matter was based on the ability of effective communication and team leader behavior. The regression coefficient was obtained at 0.77, meaning that any change in team leadership appears to clearly affect student performance as the event organizer by 77.0%.